The impact of COVID-19 pandemic on Female sexuality: an integrative review (Research, Society and Development, 2022)
Objective: to identify scientific productions in the literature that evaluated the impact of the COVID-19 pandemic on female sexuality and its related factors. Methodology: This is an integrative literature review, using the Health Sciences Descriptors (DeCS): “Coronavirus infections. Sexual behavior. Women” and its respective translations. The search was carried out through the Virtual Health Library (BVS) and the National Library of Medicine (PubMed), in addition to an exploratory search on the internet in order to increase the number of studies included in the review. The inclusion criteria were articles available in full and dealing with the theme. Exclusion criteria were: duplicate texts, literature review articles and those unrelated to the topic. Results: The search resulted in 91 articles for the first analysis and after applying the inclusion and exclusion criteria, 24 articles were selected for full reading. Ten final articles were selected. Final considerations: The study allowed us to observe how the COVID-19 pandemic caused major transformations in general in the lives of individuals. Restrictive measures such as social distancing disfavor female sexual activity, due to the decrease in encounters and the fear of contamination, interpersonal relationships were impaired, which caused a worsening in women's sexual performance.